. Advertisement .

..3..

. Advertisement .

..4..

The following article will add knowledge about “*8) Find the inverse Laplace transform** **F*(s) = cot^{-1} (s – 2)“. Let’s keep an eye on the content below!

## Question: 8) Find the inverse Laplace transform F(s) = cot^-1 (s – 2)

......... ADVERTISEMENT .........

..8..

8) Find the inverse Laplace transform

*F*(s) = cot^{-1} (s – 2)

## Answer

*F*(s) = cot^{-1}(s-2)

Because we all know this already

f(t) = L-1 [ F(s) ] = ( -1/ t) L-1[F'(s) ]

so we first calculate F'(s) ,

F'(s) = -1 / [(s-2)^2 + 1 ]

Now, put this value

f(t) = (-1/t) L-1[ -1 / [(s-2)^2 + 1 ] ]

= (1/t) L-1[1 **/** (s-2)^2 + 1]

By using the inverse laplace formula,

(e^at)sinbt = b **/**(s-a)^2 + b*b

= (1**/**t )*[(e^2t)sint ]

= (e^2t)sint **/** t

## Last words

Above is the solution of **“8) Find the inverse Laplace transform F(s) = cot^{-1} (s – 2)“**. If you have good solutions or comments, please leave a message.

## Leave a comment